Finance in an age of austerity : the power of customer-owned banks - Birchall, Johnston (United Kingdom Edward elgar publishing Ltd., 2013)
"This is a book in search of an alternative to the discredited investor-owned banks that have brought the rich countries into crisis and the world economy into a long period of austerity. It finds customer-owned banks - credit unions, co-operative banks, building societies - have hardly been affected by the crisis and continue to operate according to their organisational DNA: low-risk, close to the customer, underpinned by real savings, and still lending to SMEs to protect jobs and local economies. They are big business - in some countries with over 40% of the market - but networked in smaller, democratic societies whose origins go back to 1850s Germany. The book explores their history and current situation, measures the impact of the banking crisis, makes a systematic study of their advantages, compares them to alternatives (savings banks and micro-finance institutions), and investigates their supervision and governance structures. It provides hard evidence for the superiority of customer-owned banks." -- Back cover.
Includes bibliographical references (pages 215-228) and index.
nmn, 24/10/17, ijb 07/03/2019
Loans
Keywords: Banks and banking, Cooperative; Credit unions; Savings banks